2007
DOI: 10.1038/sj.bjc.6604008
|View full text |Cite
|
Sign up to set email alerts
|

Tea and coffee drinking and ovarian cancer risk: results from the Netherlands Cohort Study and a meta-analysis

Abstract: In a cohort study, ovarian cancer (280 cases) showed no significant association with tea or coffee, the multivariable rate ratios being 0.94 (95% confidence interval (CI): 0.89, 1.00) and 1.04 (95% CI: 0.97, 1.12) per cup per day, respectively. A meta-analysis also produced no significant findings overall, though the cohort studies showed a significant inverse association for tea. British Journal of Cancer (2007) Tea and coffee are widely consumed around the world and may affect human health. Several case-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
3
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 25 publications
7
52
3
2
Order By: Relevance
“…Previous meta-analyses reported borderline inverse associations for all tea combined (OR 0.84 [9]; OR 0.85 [8]), similar to our finding of an inverse association (albeit not statistically significant), between green tea consumption and ovarian cancer. Our case-control results for all types of tea combined are consistent with two recent meta-analyses.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Previous meta-analyses reported borderline inverse associations for all tea combined (OR 0.84 [9]; OR 0.85 [8]), similar to our finding of an inverse association (albeit not statistically significant), between green tea consumption and ovarian cancer. Our case-control results for all types of tea combined are consistent with two recent meta-analyses.…”
Section: Discussionsupporting
confidence: 92%
“…The systematic review was restricted to green tea as two recent meta-analyses have previously considered the association between consumption of all types of tea combined (in practice this was predominantly black tea) and ovarian cancer [8,9] and furthermore it is the specific polyphenols in green tea that are widely thought to possess cancer inhibitory properties [1]. Eligible studies published prior to March 2009 were identified by searching Medline 1950-(U.S. National Library of Medicine, Bethesda, MD), Embase 1966-(Elsevier Science, Amsterdam, Holland), Conference Papers Index 1982-(CSA, Bethesda, MD), ISI Science Citation Index and by hand-searching the reference lists of the retrieved articles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of these has shown significant associations between coffee consumption and ovarian cancer incidence (25,28,33,34). One of these is the previously mentioned Aichi Cancer Center study that reported no clear association between intake of coffee and risk among Japanese women among the 166 ovarian cancer cases as compared with 12,425 women free of cancer (28).…”
Section: Ovarian Cancermentioning
confidence: 94%
“…A cohort study conducted (34) in the Netherlands also observed no significant association with coffee and ovarian cancer, the multivariable rate ratios being 1.04 (95% CI = 0.97-1.12) per cup per day among the 280 ovarian cancer cases and cohort comparisons. These authors also conducted a meta-analysis and found no significant associations between ovarian cancer occurrence and coffee consumption (34) across the various studies from various populations and differing consumption patterns.…”
Section: Ovarian Cancermentioning
confidence: 99%